2018
DOI: 10.1186/s12913-018-3581-0
|View full text |Cite
|
Sign up to set email alerts
|

Elderly at risk in care transitions When discharge summaries are poorly transferred and used –a descriptive study

Abstract: BackgroundDischarge summary with medication report effectively counteracts drug-related problems among elderly patients due to insufficient information transfer in care transitions. However, this requires optimal transfer and use of the discharge summaries. This study aimed to examine information transfer with discharge summaries from hospital to primary care.MethodsA descriptive study with data consisting of discharge summaries of 115 patients, 75 years or older, using five or more drugs, collected during one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Neither can we be certain that the non-significant difference between groups in regard to transfer of information to the primary care centre is correct and there is no way of telling if the patient actually received or took part of the contents of their discharge summary or not. Previous studies do, however, show that discharge summaries are often lacking in content and quality [49,50] as is the transfer of these to the next caregiver [50]. Even though the discharge summary, medication report and medications list are considered to be helpful to the GPs, their use of the information provided is often lacking due to the uneven quality as well as the discrepancies found in the medications lists included [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither can we be certain that the non-significant difference between groups in regard to transfer of information to the primary care centre is correct and there is no way of telling if the patient actually received or took part of the contents of their discharge summary or not. Previous studies do, however, show that discharge summaries are often lacking in content and quality [49,50] as is the transfer of these to the next caregiver [50]. Even though the discharge summary, medication report and medications list are considered to be helpful to the GPs, their use of the information provided is often lacking due to the uneven quality as well as the discrepancies found in the medications lists included [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies do, however, show that discharge summaries are often lacking in content and quality [49,50] as is the transfer of these to the next caregiver [50]. Even though the discharge summary, medication report and medications list are considered to be helpful to the GPs, their use of the information provided is often lacking due to the uneven quality as well as the discrepancies found in the medications lists included [49][50][51]. These deficits lead to risks of medication errors and ADEs for older patients in transitions of care [49,52] and could be part of the reason as to why older adults living in the community with home care have increased odds of readmission as compared to those living in nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Several studies have also identified that delays in submission of discharge summaries have caused significant consequences such as an increased rate of readmission 7 and inappropriate restarting of medications, resulting in readmission and risk of medication errors. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…A small study in Sweden highlighted the risk of medication errors and drug-related problems for older people at discharge 2. It found that the discharge summaries were insufficiently used and that medication lists were not updated.…”
Section: Contextmentioning
confidence: 99%